2012
DOI: 10.2139/ssrn.2063039
|View full text |Cite
|
Sign up to set email alerts
|

Look Who’s Talking: The Impacts of the Intrahousehold Allocation of Mobile Phones on Agricultural Prices

Abstract: Using data from the Philippines, we study the impact of mobile phones on the prices agricultural producers receive for their cash crop. We first look at the impact on price of mobile phone ownership at the household level. Because this masks a considerable amount of heterogeneity, we then look at the impact on price of the intrahousehold allocation of mobile phones. We find that whether the household owns a mobile phone has no impact on price, but whether a farmer or his spouse own a mobile phone is associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Evidence emerging from micro-level studies tends to support the conjecture that mobile phones improve market efficiency (Salia, Nsowah-Nuamah, & Steel, 2011;Lee and Bellemare, 2013), leads to higher incomes for small-scale entrepreneurs (Aker, 2010;Jensen, 2007), and improves social capital (Baardewijk, 2017), quality standards for buyers, and new opportunities for financial institutions (Qiang et al, 2012). Mobile ownership has been associated with better producer prices (Lee & Bellemare, 2013). Jensen (2007) and Abraham (2007) find lower dispersion of fish prices across markets and over different periods of time for fishermen and wholesalers who used mobile phones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Evidence emerging from micro-level studies tends to support the conjecture that mobile phones improve market efficiency (Salia, Nsowah-Nuamah, & Steel, 2011;Lee and Bellemare, 2013), leads to higher incomes for small-scale entrepreneurs (Aker, 2010;Jensen, 2007), and improves social capital (Baardewijk, 2017), quality standards for buyers, and new opportunities for financial institutions (Qiang et al, 2012). Mobile ownership has been associated with better producer prices (Lee & Bellemare, 2013). Jensen (2007) and Abraham (2007) find lower dispersion of fish prices across markets and over different periods of time for fishermen and wholesalers who used mobile phones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar study in Ghana by Overa [ 31 ] indicated that farmers could be directly connected with buyers through cell phones so that they can get a better price than working through brokers. Studies by Muto and Yamano [ 32 ], Muto and Yamano [ 33 ], and Lee and Bellemare [ 34 ] show that farmers use the mobile phone to save time, money, and energy. Ndyetabula and Legg [ 35 ] further indicated that cell phone can be used to disseminate information about the outbreak of crop diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, they found evidence that farmers that received price information via SMS were less likely to sell at the farm gate and more likely to travel to more distant markets. Finally, Lee and Bellemare (2013) analysed data from the Philippines and found evidence that the use of mobile phones is associated with higher crop prices received by agricultural producers, but only once the intra-household allocation of technology is taken into account.…”
Section: Introductionmentioning
confidence: 99%